Proceedings of the International Conference on Microelectronics, Computing & Communication Systems MCCS 2015 - Nath, Vijay; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises select papers from the International Conference on Microelectronics, Computing & Communication Systems(MCCS 2015). Electrical, Electronics, Computer, Communication and Information Technology and their applications in business, academic, industry and other allied areas. The main aim of this volume is to bring together content from international scientists, researchers, engineers from both academia and the industry. The contents of this volume will prove useful to researchers, professionals, and students alike.
A Secure Three-Factor Remote User Authentication Scheme Using Elliptic Curve Cryptosystem -- Implementation of Fingerprint-Based Biometric System and Its Integration With Hrms Application At Rdcis, Sail -- Fabrication and Investigation of Low Voltage Programmable Flash Memory Gate Stac -- An Effective Method For Maintenance Scheduling of Vehicles Using Neural Network -- Universally Verifiable Certificateless Signcryption Scheme For Manet -- Impact of Sidewall Spacer Layers On The Analog/Rf Performance of Nanoscale Double-Gate Junctionless Transistors -- A Novel Data Encryption Approach In The Grid Structured Binary Image -- Analysis of Electromagnetic Wave Using Explicit FDTD in TM Mode with Extrapolation -- A Dea Based Evolutionary Computation Model For Stock Market Forecasting -- Electrical Equivalent Model For Gene Regulatory System -- Colour Image Segmentation Techniques: A Survey -- Wireless Image Sensor Networks: A Review -- Design of A Low Cost Heart Rate Monitoring System -- Design of Da Based Fir Filter Architectures Using Lut Reduction Techniques -- Fractional Delay Fir Filter Architecture Using Numeric Strength Reduction Techniques -- Lifetime Enhancement of Wsn Based On Modified Heterogeneous Leach Protocol -- Modeling and Investigation of Electrothermally Actuated Micro-Gripper -- An Ultra Low Power Internet Controlled Home Automation System -- Depth Averaged Velocity Distribution For Symmetrical and Asymmetrical Compound Channels -- A 0.533 Db Noise Figure, 7 Mw Narrowband  Low Noise Amplifier For Global Position System Application -- Design of Ultra Low Power Cmos Class E Power Amplifier -- Cryptic Mining For Automatic Variable Key Based Cryptosystem -- Single Mode Negative Dispersion Hexagonal Photonic Crystal Fiber -- Improved Clustering For Categorical Data With Genetic Algorithm -- Balanced Wrapper Design To Test The Embedded Core Partitioned Into Multiple Layer For 3d Soc Targeting Power and Number of TSVS -- Investigations On The Logic Performance of Hybrid Cmosfets Comprising P-Ge/ N-Ingaas Mosfets With  Barrier Layers -- Antenna Path Loss Propagation Model In The Dehradun Valley At 1800 Mhz In L- Band -- Reduction of Dark Current In Qwip -- Design of Circular Disc Monopole Antenna For Uwb Application.
Keywords: Electronic circuits; Telecommunication; Computational intelligence; Electronic Circuits and Systems; Communications Engineering, Networks; Computational Intelligence